ASSESSING THE HUMAN DIMENSION OF DIGITAL LEADERSHIP TO SUCCESSFUL DIGITAL TRANSFORMATION - Intan, Sarah Diba; Tjakraatmadja, Jann (LPPM STIE Muhammadiah Bandung, 2024)
All industries are experiencing significant changes due to Industry 4.0 and the upcoming Industry 5.0. These advancements will greatly impact the industry globally over the next five years. Therefore, several companies are undergoing digital transformation. Successful digital transformation relies on various factors, with leadership being crucial for setting a vision and driving change. By undertaking digital transformation, companies ensure their leaders continuously develop essential digital leadership skills. According to the assessment at PT X a state-owned enterprise in Indonesia engaged in transportation and logistics, the results indicate a gap between employees' current digital leadership competencies and the required level. This study aims to improve digital leadership competency at PT X. Objectives include identifying existing training programs, evaluating digital leadership dimensions needing improvement, and determining necessary improvements. The study uses the Digital Leadership Scale by Haroon Abbu et al. (2022), with a quantitative design involving 124 respondents. Findings show that digital leadership is part of the leadership development program, tailored to job levels from junior managers to executive presidents. The lowest scores based on assessment are in skill acquisition and courage, indicating areas for improvement. This research provides insights into digital leadership and competency improvement, crucial for successful digital transformation.